Universal Bethe Ansatz and Scalar Products of Bethe Vectors - Belliard, S.; Pakuliak, S.; Ragoucy, E. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
An integral presentation for the scalar products of nested Bethe vectors for the quantum integrable models associated with the quantum affine algebra Uq(gl₃) is given. This result is obtained in the framework of the universal Bethe ansatz, using presentation of the universal Bethe vectors in terms of the total currents of a ''new'' realization of the quantum affine algebra Uq(gl₃).